STUDY PROGRAM TRANSPORT IN CRISES SITUATIONS ON INTERNATIONAL FRAME (Perner's Contacts, 2006)
In these times there are many serious reasons to create a new study programs. University of Zilina, has many long-term experience with subjects military transport and transport in crisis or dangerous situation.